Lipase-catalysed synthesis and optimization of biologically active amides of cinnamic acid derivatives - Abu Alrub, Mohammad Hesham Abdelrahman (2013)
Natural products compounds are very important source of materials for the pharmaceutical industry. Amides are in general present in natural products. Amides play an essential role in virtually all biological processes such as enzymatic catalysis and medical chemistry. Natural products which contain amide group play an important role in modern drug discovery, especially in cancer treatment. The extracts from Litsea plants have been reported to have significant cytotoxic activity against human tumor cells. The compounds which are the major components of Litsea plants are so valuable and important to be synthesized and studied. Litsea plant consists of many cinnamic acid amides. There are no suggested methods for the synthesis of Ntrans-sinapoylmethoxytyramine and N-trans-sinapoyldimethoxytyramine. The compounds N-trans-feruloylmethoxytyramine, N-trans-sinapoyltyramine and Ntrans-feruloyldimethoxytyramine have only one method for synthesis with a low yield. N-trans-feruloyltyramine needs hydrazine as a reagent which is very dangerous. The extraction method gives very low yield and the process is not economic. Thus, it is important to find a new direct method to synthesize these compounds. Six cinnamic acid amides derivatives were successfully synthesized from the reaction of cinnamic acids with tyramine derivatives in a one-step lipasecatalyzed reaction. The use of immobilized lipase, Lipozyme TL IM as the catalyst in the reaction provides an easy isolation of the enzyme from the products and other components in the reaction mixture. All the amides were characterized using Fourier transform infrared (FTIR)spectroscopy, proton nuclear magnetic resonance (1H NMR) and carbon-13 (13C NMR) techniques. The optimized percentage yield obtained was 93.5 % when the process was carried out for 48 h, at molar ratio of tyramine HCl: cinnamic acid - 1:6 at 40 ºC. Enzymatic synthesis of N-trans-feruloyltyramine was optimized by Response Surface Methodology (RSM) using 4-hydroxy-3-methoxycinnamic acid and tyramine hydrochloride in a one-step lipase catalyzed reaction using Lipozyme TL IM. RSM based on five-level, four-variable central composite rotatable design (CCRD) was used to evaluate the interactive synthesis with variables consisting of reaction time (24-96 h), temperature (30-50 ºC), amount of enzyme (2.5-25 mg/mL)and substrate molar ratio [cinnamic acid:tyramine HCl, (1:1 - 8:1 mmol)] on the percentage yield of N-trans-feruloyltyramine. The optimum conditions derived via RSM were; reaction time, 52 h, temperature, 43 ºC, amount of enzyme, 13 mg/mL and substrate molar ratio (cinnamic acid:tyramine HCl) 6.2:1. The actual experimental yield was 96.3 % under the optimum condition, which compared well to the maximum predicted value of 97.2 %. The anticancer activities for all compounds were evaluated against human colorectal (HT-29), human estrogen-receptor positive breast cancer (MCF-7), human estrogenreceptor negative breast cancer (MDA-MB-231) and human hepatocellular carcinoma (HepG2) cell lines. It can be concluded that all the amides normalized the rate of cell growth. The antibacterial properties of the synthesized amide compounds were evaluated on gram negative bacteria, gram positive bacteria and yeast. It was found that all synthesized amides inhibited the growth of the tested bacteria and yeasts with good zone diameter. N-trans-Sinapoyldimethoxytyramine inhibited the growth of the tested gram negative with 24 mm zone. N-trans-Sinapoyltyramine inhibited the growth of the tested gram positive MRSA and yeast CA with 30 mm and 40 mm zone, respectively against the corresponding microorganisms. Antioxidant activities were studied for all the compounds using DPPH and ATBS methods. In both methods, all compounds showed potential activity. N-transsinapoylmethoxytyramine showed the highest effective activity for all the compounds. DPPH Inhibition Ratio (%) was at 69.2 % and ABTS Inhibition Ratio (%) at 79.6 %. In addition, N-trans-feruloyldimethoxytyramine showed relatively lower activity with DPPH Inhibition Ratio (%) at 59.4 % and ABTS Inhibition Ratio (%) at 72.0 %. However, these results are considered as good antioxidant activity. Kinetic study using Lipozyme TL IM in the amidation of cinnamic acid with tyramine HCl was carried out. The effect of both substrates on the initial reaction rate was studied. The initial rates of the reaction were calculated and the results showed that the amidation reaction obeyed the Ping-Pong Bi-Bi mechanism. Lineweaver-Burk plots of amidation reaction were determined. The kinetic constants of reaction were studied whereby Vmax (mmol/L/min) was 0.0328 and Km (CA)(mmol/L) was 0.8955.